2022
DOI: 10.3389/fneur.2021.752632
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Safinamide Adjunct Therapy on Depression and Apathy in Patients With Parkinson's Disease: Post-hoc Analysis of a Japanese Phase 2/3 Study

Abstract: Background and PurposeNeuropsychiatric symptoms in Parkinson's disease (PD) have been shown to significantly affect quality of life (QOL). We investigated the impact of safinamide on depression and apathy when administered as an adjunct to levodopa in Japanese patients with PD.MethodsThis was a post-hoc analysis of data from a phase 2/3 clinical study of safinamide in Japanese patients with PD experiencing wearing-off (JapicCTI-153056; https://www.clinicaltrials.jp/cti-user/trial/ShowDirect.jsp?japicId=JapicCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…In contrast to our findings, earlier studies showed SAF might suppress I Na magnitude in different preparations [ 21 , 26 – 29 ]. It will be important to determine whether the inhibitory effect of SAF on I Na is associated with either the decrease of the activity of monoamine oxidase or the production of reactive oxygen species [ 13 , 14 , 22 25 ]. Of note, although SAF was considered a potential anticonvulsant based on prior reports of I Na attenuating property, clinically, the anticonvulsive activity of SAF was not proven, as only open-label studies comparing with baseline were provided [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, earlier studies showed SAF might suppress I Na magnitude in different preparations [ 21 , 26 – 29 ]. It will be important to determine whether the inhibitory effect of SAF on I Na is associated with either the decrease of the activity of monoamine oxidase or the production of reactive oxygen species [ 13 , 14 , 22 25 ]. Of note, although SAF was considered a potential anticonvulsant based on prior reports of I Na attenuating property, clinically, the anticonvulsive activity of SAF was not proven, as only open-label studies comparing with baseline were provided [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also reported the efficacy of SAF as an add-on treatment to subthalamic nucleus deep brain stimulation [ 19 , 20 ]. SAF exerts its effects through various mechanisms, including inhibition of monoamine oxidase (MAO)-B activity [ 2 , 13 15 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“… 29 Notably, reductions in depression were associated with changes in daily ON-time of at least 1 hour, the presence of pain during the OFF-time at baseline, and female sex. 28 …”
Section: Methodsmentioning
confidence: 99%
“…27 Hattori et al did a post-hoc analysis of data from II and III-phase clinical trials, and reported that safinamide exhibited significant improvement in patients with PD experiencing wearing-off symptoms, regardless of whether they received the 50 mg or 100 mg dose. 28 The initial study focused on evaluating changes in the UPDRS Part I item 3 score (depression) and item 4 (apathy), as well as the PDQ-39" emotional well-being. 29 Notably, reductions in depression were associated with changes in daily ON-time of at least 1 hour, the presence of pain during the OFF-time at baseline, and female sex.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation